The impact of digitalization on international expansion: A study on market entry strategy based on the Integration-Responsiveness Framework - TAN, Thian Kiang (Institutional Knowledge at Singapore Management University, 2021)
Digitalization has accelerated the growth and creation of new business models. There are more unicorn companies (a non-public company valued at more than US$1B) in the last 10 years than the decades before it. The use of digital technologies presents new opportunities for digitally active firms to capture growth in a new market. This paper studies how digitalization influences the internationalization process of the firm and its mode of entry into a foreign market. Drawing on existing literature on digitalization, this paper creates a novel approach to study the effect of digitalization by classifying firms based on their market business model (B2B, B2B2C and B2C) and its inherent operation characteristics (such as process-oriented vs information-driven business). This creates a finer granular approach to investigate the effect of digitalization and its variation across different industries. This study examines the effect of digitalization on internationalization through the managerial perception of competition based on the Integration-Responsiveness framework. It uses the adoption of technology and diffusion of digital innovation as observable factors to provide the empirical data to study the effect of digitalization and its impact on the choice of mode of entry. The hypotheses on the effect of digitalization on international expansion are tested with technological and digitalization adoption data, in a sample of 535 organizations based in Singapore. The findings show that by not considering the effect of digitalization, the classical Integration – Responsiveness (IR) framework is not sufficient to describe the decision of firms, choosing greenfield venture as its preferred mode of entry, in today digital context. These findings create a new perspective on the Integration – Responsiveness (IR) framework and contribute to management research by identifying the firm-level characteristics, that amplify the effect of digitalization, which can be used to calibrate the expansion strategies for modern enterprises.